We, Not Just I, Must Trust Doctors: Network Medical Trust and Health Care Utilization - Tania Ravaei; Megan Bolton (Socius)
Previous research has demonstrated associations between social network characteristics and health care utilization. However, understanding the role of network- and individual-level factors together remains limited. We use the Person to Person Health Interview Study (2018–2020) to show network-level and individual-level predictors of two health care utilization measures: having a regular doctor (preventive care) and seeking medical services after an acute health care problem (reactive care). We explore preventive care among the full sample (N = 2,524) and reactive care among the subsample that reported a physical or mental health problem in the past year (n = 885). We measure medical trust as an individual-level characteristic (personal trust in physicians) and a network-level characteristic (average trust in physicians among social ties). Results show that higher medical trust in doctors within one’s network positively predicts both having a regular doctor and utilizing medical services after a health care problem, even after adjusting for known predictors of utilization. Our findings provide support that a network’s pro-medical culture matters beyond individual medical trust for health care utilization.